한약재 복합 추출물의 항산화 및 항염증 효과 - 이초연; Choyeon Lee; 이지혜; Jihye Lee; 박미미; Mimi Park; 박진한; Jinhan Park (大韓本草學會誌, 2025)
Objective : This study aimed to evaluate the antioxidant and anti-inflammatory effects of a combined herbal extract (PHCL), composed of Panax ginseng, Houttuynia cordata, Centella asiatica , and Lonicera japonica , and to investigate its potential as a functional ingredient in cosmetic formulations targeting inflammation and oxidative stress. Methods : The antioxidant properties of PHCL were assessed through multiple in vitro assays, including DPPH and ABTS radical scavenging activities, reducing power analysis, and the quantification of total polyphenol and flavonoid contents. Anti-inflammatory effects were examined in RAW 264.7 murine macrophages. Cell viability was evaluated using the MTT assay in both unstimulated and lipopolysaccharide (LPS)-stimulated conditions. Nitric oxide (NO) levels in culture supernatants were measured using the Griess assay. Additionally, the expression levels of inducible nitric oxide synthase (iNOS) and cyclooxygenase-2 (COX2) were determined by western blot. Results : PHCL demonstrated dose-dependent enhancement of DPPH and ABTS radical scavenging activities and reducing power. The extract also contained high levels of polyphenols (155.8 mg TAE/g) and flavonoids (185.7 mg QE/g). In LPS-stimulated macrophages, PHCL significantly inhibited NO production at non-cytotoxic concentrations and effectively suppressed iNOS protein expression. Although a reduction in COX2 expression was observed, it did not reach statistical significance. Conclusion : These findings suggest that PHCL possesses strong antioxidant and anti-inflammatory properties through the modulation of free radicals and inflammatory mediators. This supports the potential application of PHCL as a bioactive compound in functional cosmetic products aimed at protecting the skin from oxidative damage and inflammation-related conditions.